Improving the efficiency of portable anti-aircraft missile systems and air-to-air missiles and newcombat use of these missiles - Golodyaev, Alexander I. (Vojnotehnički glasnik / Military Technical Courier, 2014)
This paper shows a new way of dealing with the generators of pulsating infrared interferences and а new kind of fighting  with infrared homing seekersas well as an аnalysis of this Air Force combat means and appropriate countermeasures. It is described how to upgrade infrared homing seekers to overcome generators of pulsating infrared interferences. The article describes an original method of setting false thermal targets using termite copper-aluminum and "electron" alloy. The use of modernized types of heads against aerial targets makes generators of pulsating infrared interferences useless.
Keywords: homing seekers; Infrared; missile systems